ANALISIS KECACINGAN PADA IBU HAMIL DENGAN ANEMIA - Rian Adhitya Pradana; Sulastri -; Noor Alis (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Anemia in pregnant women is where the state of the body that contain hemoglobin less than 11g/dl were caused by deficiency of iron, folic acid, mineral and vitamins such as vitamin B12,vitamin C and the presence of chronic diseases such as pulmonary tuberculosis, intestinalworm, and malaria. The prevalence of anemia to pregnant women in Indonesia the year 2013amounted to 37.1%. Giving tablets Fe in Indonesia in 2012 has reached 85%. Based on thesurvey results Gatak Puskesmas, the number of pregnant women suffer from anemia in 2013 asmany as 77 people (8.4%) and at the end of May 2014 the number of pregnant women sufferingfrom anemia has reached 30 people. This study aims to describe of the worm infection atpregnant women with anemia in the Work Area Puskesmas Gatak. This research is a descriptivestudy using a cross-sectional approach. The number of samples of this study were 30 pregnantwomen in the Puskesmas Gatak. Sampling is total sampling by means of home visit. Resultsillustrate that describe the of pregnant women are anemic worm infection positive experience asmany as 14 people (46.7%).Keywords: anemi,  pregnant women, worm infection